Patient centered care in primary health care teleconsultations: an exploratory study - Reis, Mariana; Crispim, José; Rego, Nazaré (Procedia computer science, 2023)
With the current evolution of health digitalization driven by the COVID-19 pandemic, it is expected that teleconsultations - specifically, synchronous audio consultations (by telephone) or video-based (video calls) between health professionals (Doctors and Nurses) and patients - will be more used in Primary Health Care. The provision of health care through teleconsultations must be evaluated by the quality management of health organizations to ensure that the needs of patients are met. For this reason, this study was carried out under the objective of identifying indicators to create a culture of Patient-Centered Care (PCC) in teleconsultations in Primary Health Care. The methodology followed was based on the Delphi method. The research aimed to analyze the suitability of 48 indicators (organized in Donabedian's quality dimensions) to assess the implementation of PCC in Primary Health Care. Despite all indicators were viewed as very important, the disparity in responses was significant. Future research should extend this study by involving other groups of experts (like academics who study the subject and members of patient associations).